Web based agricultural data management system and methods of managing thereof. - Mohamed Shariff, Abdul Rashid; Mahmud, Ahmad Rodzi; Che Ya, Nik Norasma; Jahanshiri, Ebrahim; Mohd Soom, Mohd Amin; Bejo, Siti Khairunniza; Abdul Aziz, Fauzul Azhan (2010)

(untitled)
A web based agricultural data management system is provided, the system includes a server and a database network connectible to an interface terminal, wherein data is translatable to readable and viewable maps used in agriculture.